LATAR BELAKANG, WARNA DASAR, DAN PENGARUH REFORMASI PROTESTAN TAHUN 1517 | BACKGROUND, BASIC CONTOURS AND IMPACT OF THE 1517 PROTESTANT REFORMATION - George Ludwig Kirchberger (Institut Filsafat dan Teknologi Kreatif Ledalero, 2017)
Abstract: This article illustrates the background of. and reasons for, the Reformation, the basic contours of Luther’s theology and the Reformation movement he initiated, and the influence of the Reformation movement on the present situation. A brief description of the post-Reformation inter-Christian Church controversies for approximately 400 years is also presented, highlighting the fact that the theology of the time was unaware of the contextual influence of a text as the deepest reason for the controversy. The hermeneutical consciousness of the twentieth century led theology to overcome various inter-Christian Church controversies by showing that different and seemingly contradictory formulas could express the same truth, provided that each was placed in its original context. The author proposes as an example of the influence of the events of the Reformation on the present situation, the very important issue of religious freedom in situations such as Indonesia with a variety of religions and beliefs. In concluding the author gives advice on how different Christian Churches can learn from each other, so that they remain active in renewing the Church according to the ecclesia semper reformanda principle. Keywords: Reformation, Martin Luther, ecumenical, interChristian Church relationship, World Council of Churches. Abstrak: Artikel ini menggambarkan latar belakang dan alasan peristiwa Reformasi, warna dasar teologi Luther dan gerakan Reformasi yang dibangunnya, serta pengaruh gerakan Reformasi terhadap situasi dewasa ini. Deskripsi singkat kontroversi antar-Gereja Kristen pasca-Reformasi selama kurang lebih 400 tahun juga dimuat di sini dengan menampilkan kenyataan bahwa teologi waktu itu tidak menyadari pengaruh konteks atas suatu teks sebagai alasan terdalam lahirnya kontroversi itu. Kesadaran hermeneutis membuat teologi pada abad XX itu sanggup mengatasi pelbagai kontroversi antar-Gereja Kristen dengan membuktikan, rumusan yang berbeda dan bertentangan bisa menyatakan kebenaran yang sama, asalkan masing-masing ditempatkan dalam konteksnya yang asli. Sebagai suatu contoh pengaruh peristiwa Reformasi atas situasi dewasa ini, pengarang mengemukakan kebebasan beragama yang sangat penting dalam situasi seperti di Indonesia dengan anekaragam agama dan kepercayaan. Pada tempat terakhir penulis memberikan anjuran tentang bagaimana Gereja-gereja Kristen yang berbeda bisa saling belajar, agar mereka tetap aktif membarui Gereja seturut prinsip ecclesia semper reformanda. Kata-kata kunci: reformasi, Martin Luther, ekumene, relasi antar-Gereja Kristen, World Council of Churches.